2003
DOI: 10.1046/j.1525-1470.2003.20402.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Discoid Lupus Erythematosus: A Tunisian Retrospective Study of 16 Cases

Abstract: Discoid lupus erythematosus (DLE) is uncommon in children. The clinical features of childhood DLE are similar to those of adult DLE in presentation and chronic course. However, children have a particularly high level of transition to systemic disease. We undertook a retrospective study of 16 children with DLE ranging in age from 2 to 15 years, seen over a 9-year period. Six were less than 10 years old at the onset of the disease. The sex ratio was equal. The frequency of childhood DLE was about 7% of the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1
12

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 18 publications
1
23
1
12
Order By: Relevance
“…15,[21][22][23]26 Overall, 38% of patients developed SLE, 15% of whom were given the diagnosis of DLE as a manifestation of concurrent SLE and 26% of whom developed progression to SLE, consistent with the up to 25% rate of progression noted in prior pediatric studies of DLE. 15,23,27 Patients with SLE progression were at greatest risk within the first year after diagnosis, although mean follow-up duration was limited to 5.0 years.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…15,[21][22][23]26 Overall, 38% of patients developed SLE, 15% of whom were given the diagnosis of DLE as a manifestation of concurrent SLE and 26% of whom developed progression to SLE, consistent with the up to 25% rate of progression noted in prior pediatric studies of DLE. 15,23,27 Patients with SLE progression were at greatest risk within the first year after diagnosis, although mean follow-up duration was limited to 5.0 years.…”
Section: Discussionsupporting
confidence: 70%
“…15,21 The natural history in children remains poorly understood. Small studies have demonstrated a significantly higher early rate of progression to SLE (up to 25%) during a variable follow-up duration of months to years, 15,[21][22][23] suggesting that age of onset may modify the disease severity, pattern of organ involvement, and serologic findings. The interval from diagnosis of DLE to SLE has not been well studied because of the small number of studies and limited follow-up.…”
mentioning
confidence: 99%
“…İmmunfloresan incelemede 6 haftadan eski lezyonların %80'ninde dermoepidermal bileşkede kompleman veya immunglobulin birikimi gözlenir. Yine de immun birikim olmaması tanıyı dışlamaz (1,3,4,6). Laboratuvar parametreleri tam kan sayımı, serum biyokimyasal analizi, sedimentasyon hızı, C-reaktif protein, DLE'li erişkin hastaların %5'inde sistemik forma dönüşüm görülür.…”
Section: Discussionunclassified
“…Among adults with DLE, less than 5% patients develop the disease before 16 years and less than 3% develop it before 10 years of age. [34] Childhood onset DLE has a higher chance of developing systemic disease. The aim should be to treat lesions of DLE at an early stage to prevent scarring.…”
Section: Introductionmentioning
confidence: 99%